2003
DOI: 10.1002/hpm.711
|View full text |Cite
|
Sign up to set email alerts
|

Cost analysis of pneumonia treatment in the Philippines

Abstract: The objectives of this study were to describe the cost distribution of pneumonia treatment in tertiary hospitals in the National Capital Region (NCR) and to identify variations in costs in order to provide basic information to the Philippine Health Insurance Corporation (PHIC) for quality assurance and policy development. This study focuses on 3861 reimbursement claims, which come from 22 government and 38 private tertiary hospitals. Wide variations of cost existed among the hospitals and among the inpatients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
(12 reference statements)
0
2
0
1
Order By: Relevance
“…Estas diferencias se explican por los rubros de medicamentos, servicios complementarios y pruebas diagnósticas, lo que concuerda con los resultados de estudios similares (16,17). El dato de que las estancias en la UCI se explican esencialmente por los casos presuntamente bacterianos apoya también el uso de la radiografía de tórax como recurso diferenciador para estudios epidemiológicos o de costos.…”
Section: Discussionunclassified
“…Estas diferencias se explican por los rubros de medicamentos, servicios complementarios y pruebas diagnósticas, lo que concuerda con los resultados de estudios similares (16,17). El dato de que las estancias en la UCI se explican esencialmente por los casos presuntamente bacterianos apoya también el uso de la radiografía de tórax como recurso diferenciador para estudios epidemiológicos o de costos.…”
Section: Discussionunclassified
“…In a study of pneumonia, it was revealed that private hospitals are more expensive than their counterpart government hospitals (Liu et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Human milk contains a wealth of immunologic factors that fight against infections during infancy, and breast milk has evolved to provide the best nutrition, immune protection, regulation of growth, development and metabolism for the human infant. 3 The predominant antibody in breast milk-secretory IgA, confers its immune protection by inhibiting the adherence to or penetration of the gastrointestinal tract by pathogens and by phagocytosis of pathogens. Secretory IgA also provide immunological protection to the infant, whilst its own immune system matures.…”
Section: Introductionmentioning
confidence: 99%